Effect of object shape on the flow past microstructures in small channel - Mule, Gunwant M.; Kulkarni, Amol A. (Fluid Dynamics Research, 2021)
Flow past objects in microfluidics and microscale devices are used to perturb the flow and thereby achieve effective mixing and heat transfer. This paper presents the observations on the flow past bluff (elliptical, rectangular and triangular) cylindrical micropillars (objects) having different cross-sectional area in a micro-channel through 2D simulations. The pertinent range of Re based on object dimension (0.1 Re 150) was chosen to understand the wake dynamics that would remain relevant for comparison with literature data. Drag coefficient, recirculation region, critical Reynolds number for flow oscillations and vortex strength in a channel were studied. The drag coefficient was found to increase with aspect ratio of the object. The critical Re for flow oscillations was found to increase with the cross-sectional area of the object. The vortex strength in a channel was seen highest for triangular cylinder compared to elliptical and rectangular cylinder.
Keywords: 2D simulations; flow past objects; micro and mini-channels; micropillars; wake dynamics